2017
DOI: 10.1080/00325899.2017.1280585
|View full text |Cite
|
Sign up to set email alerts
|

Sintering behaviour and mechanical characterisation of Ti64/xTiN composites and bilayer components

Abstract: Ceramic particle reinforcement can be used to improve the surface properties of Ti6Al4V (Ti64) alloy. Powder metallurgy route is a promising method to fabricate such reinforced Ti64 components. To assess the relevance of this technique, this work investigates the effect generated by the addition of TiN particles in Ti64 powder during free sintering. TiN reinforcement particles were randomly distributed in the Ti64 matrix with three different concentrations in two configurations: completely reinforced and unrei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…In this study a sintering temperature of 1200 ∘ C was used as the purpose is to keep a microporous network thanks to partial sintering. Indeed, Chávez et al showed that using a sintering temperature of 1200 ∘ C led to around 11 % of porosity in Ti64 samples with particle shape and size similar to the ones used here [70]. Figure 6 shows the scaffold aspect at each processing step (dried, debinded, sintered).…”
Section: Thermal Treatmentsmentioning
confidence: 71%
“…In this study a sintering temperature of 1200 ∘ C was used as the purpose is to keep a microporous network thanks to partial sintering. Indeed, Chávez et al showed that using a sintering temperature of 1200 ∘ C led to around 11 % of porosity in Ti64 samples with particle shape and size similar to the ones used here [70]. Figure 6 shows the scaffold aspect at each processing step (dried, debinded, sintered).…”
Section: Thermal Treatmentsmentioning
confidence: 71%
“…Titanium and its alloys are commonly used in the field of modern biomedicine and for the manufacturing of implants due to their biocompatibility, superior corrosion resistance, and static and fatigue strength [1][2][3]. However, some health problems related to the release of metallic ions exist, which could lead to adverse reactions and implant failure [4].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is evident from the figure 5(b) that the porosity value after sintering at 550°C is only 16.4%, compared to 19% obtained after 450°C. This conclusion is justified by the diffusion phenomenon which is thermally activated according to many authors [4,39,40,42,43]. In this regard, they explained that the best particle bonding is taking place at a high temperature, and consequently, the pore reduction has a direct relationship with the sintering process.…”
Section: Resultsmentioning
confidence: 95%